Archaeal S-layer glycoproteins: post-translational modification in the face of extremes - Kandiba, Lina; Eichler, Jerry (Frontiers in Microbiology, 2014)
Corresponding to the sole or basic component of the surface (S)-layer surrounding the archaeal cell in most known cases, S-layer glycoproteins are in direct contact with the harsh environments that characterize niches where Archaea can thrive. Accordingly, early work examining archaeal S-layer glycoproteins focused on identifying those properties that allow members of this group of proteins to maintain their structural integrity in the face of extremes of temperature, pH and salinity, as well as other physical challenges. However, with expansion of the list of archaeal strains serving as model systems, as well as growth in the number of molecular tools available for the manipulation of these strains, studies on archaeal S-layer glycoproteins are currently more likely to consider the various post-translational modifications these polypeptides undergo. For instance, archaeal S-layer glycoproteins can undergo proteolytic cleavage, both N- and O-glycosylation, lipid-modification and oligomerization. In this mini-review, recent findings related to the post-translational modification of archaeal S-layer glycoproteins are considered.